Unlocking Plum Genetic Potential: Where Are We At? - Francesco Sottile; Chiara Caltagirone; Giovanna Giacalone; Cristiana Peano; Ettore Barone (Horticulturae, 2022)
Plums are a large group of closely related stone fruit species and hybrids of worldwide economic importance and diffusion. This review deals with the main aspects concerning plum agrobiodiversity and its relationship with current and potential contributions offered by breeding in enhancing plum varieties. The most recent breeding achievements are revised according to updated information proceeding from relevant scientific reports and official inventories of plum genetic resources. A special emphasis has been given to the potential sources of genetic traits of interest for breeding programs as well as to the need for efficient and coordinated efforts aimed at efficaciously preserving the rich and underexploited extant plum agrobiodiversity. The specific objective of this review was to: (i) analyze and possibly evaluate the degree of biodiversity existing in the cultivated plum germplasm, (ii) examine the set of traits of prominent agronomic and pomological interest currently targeted by the breeders, and (iii) determine how and to what extent this germplasm was appropriately exploited in breeding programs or could represent concrete prospects for the future.